Measurements of Pupillary Diameter and Wavefront Aberrations in Pregnant Women - Yesim Altay; Mehmet Metin Altay; Gulizar Demirok; Ozgur Balta; Hulya Bolu (Scientifica)
Purpose. To show whether pregnancy affects the measurements of pupillary diameter and wavefront (WF) aberrations. Methods. This was a case-control study including 34 healthy pregnant women in the third trimester and age-matched 34 nonpregnant women. Only women who had no ocular abnormalities and no refractive error were included. We measured photopic and mesopic pupil diameter and WF aberrations at the third trimester and at the second postpartum month. Measurements of the right eyes were used in this study. The differences between groups were analysed by paired t-test and t-test. Results. Pregnant women’s mean photopic pupil size in the third trimester was significantly higher than in postpartum period and in control group (3.74 ± 0.77, 3.45 ± 0.53, and 3.49 ± 0.15 mm, p<0.05, resp.). Mesopic pupil size in the third trimester was also higher than in postpartum period and in control group (6.77 ± 0.52, 6.42 ± 0.55, and 6.38 ± 0.21 mm, p<0.05, resp.). RMS-3 and RMS-5 values were higher in pregnancy but these differences were not statistically significant. Conclusion. Pregnancy increased photopic and mesopic pupil size significantly but did not increase wavefront aberrations notably. Increased pupil size may be due to increased sympathetic activity during pregnancy. And this activity can be noninvasively determined by measuring pupil size.